2018
DOI: 10.1103/physrevx.8.031059
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-Induced Site-Selective Mott Insulator-Metal Transition inFe2O3

Abstract: We provide experimental and theoretical evidence for a pressure-induced Mott insulator-metal transition in Fe 2 O 3 characterized by site-selective delocalization of the electrons. Density functional plus dynamical meanfield theory (DFT þ DMFT) calculations, along with Mössbauer spectroscopy, x-ray diffraction, and electrical transport measurements on Fe 2 O 3 up to 100 GPa, reveal this site-selective Mott transition between 50 and 68 GPa, such that the metallization can be described by ð VI Fe 3þHS Þ 2 O 3 ½R… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
44
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 57 publications
9
44
2
Order By: Relevance
“…These electronic transformations in Fe 3 O 4 coincide with another structural phase transition to the post-postspinel Pmma structure. All these features are characteristics of the multistage correlation breakdown process, confirming the concept of a site-selective Mott transition proposed recently in [44].…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…These electronic transformations in Fe 3 O 4 coincide with another structural phase transition to the post-postspinel Pmma structure. All these features are characteristics of the multistage correlation breakdown process, confirming the concept of a site-selective Mott transition proposed recently in [44].…”
Section: Discussionsupporting
confidence: 87%
“…Thus, these postspinels remain, up to the highest pressures measured, semiconducting and paramagnetic with a mixed spin state: S = 5/2 and S = 1/2 for Fe 3+ populating eightcoordination and six-coordination sites, respectively. Recent studies of Fe 2 O 3 , hematite [44], provide experimental and theoretical evidence for a possible site-selective multistage correlation breakdown. They show that, in a material with a complex crystal structure, containing transition metal cation(s) in different environments (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…The positions of the impurity atoms (Mg/Fe) were arranged to maximize the distance from each other [74] (Fe/Mg atoms are uniformly distributed over the unit cell; that is, we neglect the possible formation of the Fe/Mg clusters under pressure [75]). For simplicity, we neglect the local relaxation effects around the impurity Mg/Fe atoms, as well as the possible formation of a site-selective Mott-insulating phase with coexisting (within a unit cell) HS and LS iron sites [76]. In order to evaluate pressure, we fit our total-energy results to the third-order Birch-Murnaghan equation of state [77] separately for the HS and LS volume regions.…”
Section: Methodsmentioning
confidence: 99%
“…After DMFT had opened the way to study multi-band models, an "orbital selective" Mott MIT was identified [48]. Then, with the advent of DFT+DMFT, a "site selective" Mott MIT was found in Fe 2 O 3 [49]. We now illustrate the DFT+DMFT approach by its application to two paradigmatic materials, SrVO 3 and Fe.…”
Section: Dft+dmft and Gw+dmft Approachmentioning
confidence: 91%